2023
DOI: 10.5455/jabet.2023.d116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of multidrug-resistant Escherichia coli isolated from human urine infections with their antibiogram profile

Abstract: Urinary tract infections (UTIs) are the leading cause of hospitalization due to bacterial infection, and the frequency of multidrug-resistant Escherichia coli isolates from these infections is increasing worldwide. The current study aims to isolate and characterize antibiotic-resistant Escherichia coli and their antibiogram typing from urine samples of humans. From April to December 2019, a total of 60 human urine samples were collected aseptically and treated to primary isolation by propagation in nutrient br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The increasing tendency of MDR strains over time, variations in the study period, and variances in the study population could all contribute to the fluctuation in the prevalence of MDR isolates. This study showed that 85.4% of E. coli, 80% of K. pneumoniae, and 90.9% of P. aeruginosa isolates were MDR, which is almost identical to the previous study's findings [52,60]. On the contrary, 100% of E. faecalis and 85.7% of S. aureus were MDR, which is higher than the earlier studies [52,13].…”
Section: Discussionsupporting
confidence: 86%
“…The increasing tendency of MDR strains over time, variations in the study period, and variances in the study population could all contribute to the fluctuation in the prevalence of MDR isolates. This study showed that 85.4% of E. coli, 80% of K. pneumoniae, and 90.9% of P. aeruginosa isolates were MDR, which is almost identical to the previous study's findings [52,60]. On the contrary, 100% of E. faecalis and 85.7% of S. aureus were MDR, which is higher than the earlier studies [52,13].…”
Section: Discussionsupporting
confidence: 86%
“…E. coli frequently causes urinary tract infections, but the therapy option is becoming more limited due to the spread of these multidrug-resistant forms of bacteria [4,19]. Since these bacteria produce biofilms and are resistant to numerous medications, continuous surveillance of antimicrobial resistance and alternative strategies for treating UTIs and other bacterial illnesses are urgently required.…”
Section: Discussionmentioning
confidence: 99%